2004
DOI: 10.1001/jama.291.11.1350
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Hypertonic Saline Resuscitation of Patients With Hypotension and Severe Traumatic Brain Injury

Abstract: EVERE TRAUMATIC BRAIN INJURY (TBI) is common in patients with major trauma and typically involves young adult men. 1 Despite current management strategies, patients with severe TBI have a high mortality rate (31%-49%) and a large number of survivors have persistent severe neurological disability. 1-4 There are 80000 to 90 000 were cases of survivors with long-term disability after head injury annually in the United States. 5 The mean lifetime cost of each TBI survivor with severe disability from TBI exceeds US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
191
3
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 423 publications
(209 citation statements)
references
References 20 publications
1
191
3
14
Order By: Relevance
“…The GOS and GOSE have been used extensively in Australian studies that assessed early interventions [76][77][78][79][80] and examined the effects of genetic status 75,81 , psychiatric disorders 82,83 , demographics, injury severity and rehabilitation 74,84-88 on outcome. The Victorian State Trauma Registry also involves use of the GOSE to assess outcome in general trauma victims, including those with TBI 89 .…”
Section: [H1] International Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GOS and GOSE have been used extensively in Australian studies that assessed early interventions [76][77][78][79][80] and examined the effects of genetic status 75,81 , psychiatric disorders 82,83 , demographics, injury severity and rehabilitation 74,84-88 on outcome. The Victorian State Trauma Registry also involves use of the GOSE to assess outcome in general trauma victims, including those with TBI 89 .…”
Section: [H1] International Developmentsmentioning
confidence: 99%
“…In many studies, the scale has been dichotomized, leading to reduced sensitivity. The point of dichotomization has varied: in some studies of medical interventions, a GOSE ranking of 5-8 has indicated a good outcome [76][77][78]80 , whereas in some studies of rehabilitation , rankings of 7-8 were good outcomes 74,75 . Not all of these dichotomizations are necessarily sensible:…”
Section: [H1] International Developmentsmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37] All studies were published in English. Of the 11 studies, only 3 included more than 100 patients 27,31,32 ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…30 In one study, three patients (0.01% of our total population) with stroke were also included, which represented less than 15% of that study's patient population. 34 Three comparators were identified: hyperosmolar solution (mannitol or sodium bicarbonate), 28,[33][34][35]37 iso-osmolar solution (normal saline or ringer's lactate), 27,31,32 and hypo-osmolar solution 36 (see Table 1). …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation